(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2011)
The present paper’s aim is to outline a definition of “analyticity” through assuming a framework whose basic concepts are taken from rhetoric. Thus, assuming particular examples from the history of analytic philosophy – i.e. philosophers that are commonly considered “analytic” - the author shows how many shared patterns are recognisable within their argumentations, explanations, beginnings and conclusions. A previous extensional definition of “analytical philosophy” is not assumed; hence the concluded remarks can be taken as features of any analytic philosopher.